2023
DOI: 10.1002/mbo3.1342
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pH‐dependent activities of virulence factors secreted by Candida albicans

Abstract: Candida albicans is an opportunistic pathogen that can thrive under adverse conditions including suboptimal pH, nutrient scarcity, and low levels of oxygen. Its pathogenicity is associated with the production of virulence factors such as extracellular hydrolytic enzymes and toxins. This study was aimed at determining the effect of external pH, substrate nature, and strain origin on protease, lipase, and hemolysin production. To achieve this objective, agar plate assays were performed at pH 5.0, 6.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…The initial pH values of the culture medium used in our experiment also corresponded to the saliva recorded, which is normally ranged from 5.6 to 7.1, including for denture wearers [73,74]. However, the presence of Candida species promotes the lowering of pH values by producing cetate; pyruvate; formate; and propionate acids, which influence in vitro tests and under clinical conditions may activate candidal proteases; phospholipases; and collagenases, promoting tissue damage and subsequent invasion by yeast-like fungi [75,76]. The possibility of the pH values of the culture medium used in studies influencing the penetration of C. albicans into soft lining remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The initial pH values of the culture medium used in our experiment also corresponded to the saliva recorded, which is normally ranged from 5.6 to 7.1, including for denture wearers [73,74]. However, the presence of Candida species promotes the lowering of pH values by producing cetate; pyruvate; formate; and propionate acids, which influence in vitro tests and under clinical conditions may activate candidal proteases; phospholipases; and collagenases, promoting tissue damage and subsequent invasion by yeast-like fungi [75,76]. The possibility of the pH values of the culture medium used in studies influencing the penetration of C. albicans into soft lining remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…3 Especially under acidic conditions, the growth of C. albicans is more vigorous, 25 and the expression level of phospholipase and other virulence factors significantly increases. [2][3][4]22,26 It has been reported that an acidic environment can reduce the antifungal activity of KET, and the low antifungal activities of crude KET are related possibly to the increase in its piperazine base protonation rate with a reduction in pH. 9 Therefore, we also evaluated the antifungal activity of KET and KET-nHLCs at pH 4.5 (Fig.…”
Section: In Vitro Antifungal Testmentioning
confidence: 99%
“…It is well established that C. albicans adapts to a wide range of pH environments, where low pH is often significant due to its relationship with serious infection. 1,2 Acidic environments increase the secretion of phospholipases and other virulence factors, which contribute to the invasion of host tissues. [2][3][4] pH is also a potent regulator of the transition of yeast into filamentous hyphae, where an acidic environment favors yeast growth, while neutral and alkaline environments favor hyphae growth and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations